2008
DOI: 10.1088/0953-8984/20/45/452201
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic phase transitions in the ternary iron arsenides SrFe2As2and EuFe2As2

Abstract: The structural and magnetic phase transitions of the ternary iron arsenides SrFe 2 As 2 and EuFe 2 As 2 were studied by temperature-dependent x-ray powder diffraction and 57 Fe Mössbauer spectroscopy. Both compounds crystallize in the tetragonal ThCr 2 Si 2 -type structure at room temperature and exhibit displacive structural transitions at 203 K (SrFe 2 As 2 ) or 190 K (EuFe 2 As 2 ) to orthorhombic lattice symmetry in agreement with the group-subgroup relationship between I4/mmm and F mmm. 57 Fe Mössbauer sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
204
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 240 publications
(236 citation statements)
references
References 34 publications
(58 reference statements)
29
204
0
1
Order By: Relevance
“…28 An analysis for a second-order transition leads to a discrepancy of at least one order of magnitude between calculated and observed specific heat anomaly. Therefore this comparison supports the first-order nature of the transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 An analysis for a second-order transition leads to a discrepancy of at least one order of magnitude between calculated and observed specific heat anomaly. Therefore this comparison supports the first-order nature of the transition.…”
Section: Resultsmentioning
confidence: 99%
“…12,14,17 Results from specific heat, magnetic susceptibility and resistivity, 7 as well as X-ray, neutron diffraction, muon-spin relaxation, and Mössbauer experiments indicate a first-order nature of the transition at T 0 . 18 However, Tegel et al 28 conclude a second-order type of the transition from their temperature-dependent X-ray powder diffraction and Mössbauer spectroscopy. To get a further insight in the nature of the phase transition, we analyzed the slope of our T 0 (p) data at p = 0 utilizing the Clausius-Clapeyron equation dT /dp = T ∆V /∆H applicable for a first-order phase-transition.…”
Section: Resultsmentioning
confidence: 99%
“…EuFe 2 As 2 , first synthesized in late 1970s, [15] is a unique "122" compound which shows both SC in the FeAs-layers upon appropriate doping, and long-range magnetic ordering in the Eu sublattice. It was found that the undoped parent compound undergoes antiferromagnetic (AFM) ordering in the Fe sublattice at 200 K, followed by another AFM ordering in the Eu sublattice at 20 K. [16,17,18,19] The two subsystems are hardly coupled, as evidenced from optical [20] and photoemission [21] studies. The magnetic structure of the latter AFM order had been proposed to be of A-type, [17,22] in which Eu 2+ spins algin ferromagnetically in the basal planes but antiferromagnetically along the c-axis, which was then confirmed by the magnetic resonant x-ray scattering [23] and neutron diffraction [24] experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that there is considerable orbital-dependent reconstruction of the electronic configuration across the magnetostructural transition [4][5][6]. Therefore, unsurprisingly several groups carrying out Mössbauer measurements have observed a singlet at room temperature, characteristic of a paramagnetic compound, and a magnetically split sextet at low temperatures [5,[8][9][10][11][12][13][14][15]. The magnetism is centered on the Fe and not on the Ba or As.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is replete with observations of well resolved sextets for several other 122 compounds of the form REFe 2 As 2 also, where RE = Eu, Sr or Ca, presumably because of traces of adsorbed O 2 (e.g. [5,[8][9][10][11][12][13][14][15]). …”
Section: Introductionmentioning
confidence: 99%